Carbothermal reduction of red mud for iron extraction and sodium removal - Feng Huaixuan; She Xue-feng; You Xiao-min; Zhang Guang-qing; Wang Jing-song; Xue Qing-guo (High Temperature Materials and Processes, 2022)
In this work, the technology of carbothermic reduction was used to extract iron and remove sodium from red mud. The effect of various parameters like reduction time, temperature, and basicity on melting separation and de-alkalization was studied. At the optimum reduction temperature of 1,450°C, the basicity of 1.5, and reduction time of 12 min, the metallization rate and sodium removal reach 96.63 and 90.62%, respectively. Melting and separating conditions gradually improve with the temperature increasing from 1,350 to 1,450°C. At high basicity (R = 2), the condition of melting and separation is poor due to a large amount of Ca2Al2SiO7 produced, which has a high melting point. Subsequently, in order to explore the aggregation state of iron ions under different basicities, the microstructure of pellets was observed by scanning electron microscopy. It was found that when the basicity is 1.5, the aggregation degree of iron particles significantly increases. X-ray diffraction (XRD) analyses of the reduced pellets indicated that at different basicities, the final phase composition of reduced pellets is mainly Ca2Al2SiO7, which is the basic material for preparing cement materials and glass ceramics. Thus, the carbothermic-reduction method is a sustainable process for dealing with the Bayer bauxite residue.